The Effect of Interactive Video Learning Media on the Motivation of Arabic Language Learning of Class VIII Students of Mts Al-Khairat Paguyaman - Mou, Zeindri; Damhuri, Damhuri; Nur iman, Muhammad (Al-Kalim : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
In the learning process, teachers are required to be able to choose the right learning media in delivering teaching materials to students, so that students more easily understand and recall the teaching materials delivered by the teacher, and make an appeal to students to be more active in following the learning process, video media is one of the media that can convey teaching materials well and interestingly. In this study aims to determine how student learning motivation before and after using interactive video learning media in Arabic language subjects. This type of research is experimental research and uses the One- Group Pretest-Posttest Design research design, which can compare the situation before and after being treated. The results of the research that the author did, namely, that video learning media has an influence on student learning motivation in Arabic language subjects, based on the results of the analysis that there is an influence of video learning media on student learning motivation in Arabic language subjects, this can be seen in the Paired 1 Statistical test obtained Sig value. (2-tailed) of 0.000 <0.05 and the analysis of the average score on the pre-test gets an average score of 46.93 and on the post-test gets an average score of 54.17.